RIGS16-248-0412: V-logging and citizenship: the Malaysian experience - Mohamed, Shafizan; Tengku Mohd Azzman, Tengku Siti Aisha (2019)
This research examined the relationship between vlogging and citizenship in Malaysia. Despite strict legal restrictions, Malaysians have taken their political discourses online and are challenging the contested freedom of speech and expression. Vlogging, in particular, enabled everyday Malaysians to become interactive social activists and political actors. By capturing this complex dynamics, this research provided a contextualized analysis of the many factors that build the vlogging-citizenship connection in Malaysia. Among others, it discussed the role of the Malaysian socio-political and media system in shaping the vlogging experience as well as the features of the vlogging technology that are changing the established Malaysian cultural and political traditions.